Kenya : Request for Disbursement Under the Rapid-Access Component of the Exogenous Shocks Facility; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Kenya. (IMF Staff Country Reports; Country Report ;, 2009)
Kenya's strong economic performance in recent years with real GDP growth of 6 percent on average over 2004-07 has been stalled by a series of exogenous but temporary shocks that hit the economy in 2008. The staff report highlights Kenya's request for Disbursement under the Rapid-Access Component of the Exogenous Shocks Facility. Monetary policy has been eased to support economic activity and fiscal policy focused on reprioritizing expenditure. Structural policies have focused on improving the food distribution mechanism for better access to staples for an estimated 10 million food-deficient Kenyans.